Rational design of PAN:P(VP-co-VAC) polymer blend gel electrolyte incorporating functional additives for dye-sensitized solar cells / Norshahirah Mohamad Saidi - Norshahirah , Mohamad Saidi (2022)
Today, the demand for clean and sustainable energy keeps increasing. Fossil fuels are the most common energy source used to generate electricity. The usage of fossil fuels leads to excessive emission of greenhouse gases and global warming. Therefore, dye-sensitized solar cell (DSSC) will be an option by most of the community as it is the most efficient, clean, sustainable, and reliable energy source. It is also cost-effective, easy to assemble, and functions under a wide range of light illumination including dim light. Unfortunately, DSSC-based polymer electrolytes have a major challenge in commercialization due to inadequate photovoltaic conversion efficiency (PCE). To address this issue, the introduction of blending host polymers such as polyacrylonitrile (PAN) and poly(1-vinyl pyrrolidone-co-vinyl acetate) (P(VP-co-VAc)) through a physical blending with various functional additives is an attractive initiative. Blending host polymer is less time-consuming method in the production of new material with desirable properties by combining the advantages of the individual polymer. The best ratio of PAN and P(VP-co-VAc) in the ethylene carbonate (EC) - propylene carbonate (PC) binary organic solvents have been determined based on their appearance and performance. It was found that 50:50 wt. % of PAN:P(VP-co-VAc) polymer blend had met the criteria where it formed a homogeneous gel mixture and high ionic conductivity of 1.51×10-5 S cm-1. Herein, three different functional additives were added into the optimized PAN:P(VP-co-VAc) host polymer blend. For the first system, the polymer blend gel electrolytes were formulated by adding different concentrations of iodide/tri-iodide redox couple. Sodium iodide (NaI) salt and iodine (I2) were used as the source of iodide/ tri-iodide. It was reported that electrolyte consist of 40 wt. % of NaI salt shows the highest ionic conductivity and PCE of 3.54×10-5 S cm-1 and 3.04 %, respectively. In the next electrolyte system, cobalt oxide (Co3O4) nanoparticles synthesized via sonochemical and co-precipitation (for the sake of comparison) were added into the optimized polymer blend gel electrolytes which consisting of 40 wt. % NaI salt. The sonochemical method was successfully reduced the crystallite size and increased the surface area of Co3O4 nanoparticles. Hence, the electrolyte containing 3 wt. % of sonochemically synthesized Co3O4 nanoparticles delivers the highest ionic conductivity and PCE of 4.62×10-5 S cm-1 and 6.46 %, respectively. The last electrolyte system, 4-tert-butyl-pyridine (TBP) was chosen as the next functional additive. The result reported that the ionic conductivity values show a significant change after the addition of TBP into the formulated polymer blend gel electrolytes employed with 3 wt. % sonochemically synthesized Co3O4 nanoparticles. Besides, the addition of TBP had a positive influence on the open-circuit voltage, (VOC) of the DSSC. The VOC increased from 610 to 750 mV after the addition of 7 wt. % of TBP. But high TBP content has reduced the short-circuit current (JSC) value. Considering all the DSSC parameters, the cell using an electrolyte containing 3 wt. % of TBP resulted in the highest PCE of 8.11 % under light illumination of 100 mW cm-2.